EYE CONTROLLED MOUSE CURSOR FOR PHYSICALLY DISABLED INDIVIDUAL - Bollam, kiran Kumar (International Journal of Psychosocial Rehabilitation, 2020)
The field of Human-Computer Interaction (HCI) is a interface how to interact with the computer. The people with eye neurolocomotor disabilities to operate computer system like normal people. A high number of people, affected with neurolocomotor disabilities or those paralyzed by injury cannot use computers for basic tasks such as sending or receiving messages, browsing the internet, watch their favorite TV show or movies. For these people we require separate interface with the system. To overcome this problem, we proposed system a new computer interface software . Through a previous research study, it was concluded that eyes are an excellent candidate for ubiquitous computing since they move anyway during interaction with computing machinery. Using this underlying information from eye movements could allow bringing the use of computers back to such patients. The researchers in this field have also explored the potential of ‘eye-gaze’ as a possible means of interaction. Some commercial solutions have already been launched, but they are as yet expensive and offer limited usability. For this purpose, we propose a mouse gesture control system which is completely operated by human eyes only. This present work objective is to present a low cost real time system for eye gaze based human-computer interaction. An open-source generic eye-gesture control system is developed, that can effectively track eye- movements and enable the user to perform actions mapped to specific eye movements/gestures by using computer webcam based on harr-cascade algorithm, hough transform algorithm and support vector machine algorithm. It detects the pupil from the user’s face and then tracks its movements. The accuracy for this work is 92%.